ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEMUNGKINAN TERJADINYA SALAH KELOLA ASET TETAP DITINJAU DARI PERSPEKTIF FRAUD DIAMOND THEORY (STUDI EMPIRIS PADA PERANGKAT DAERAH KABUPATEN SEMARANG) - Ambarwati, Juni; Handayani, Rr Sri (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2018)
This study aims to analyze the factors that influence the occurance possibility ofmismanagement of fixed assets by the state civil apparatus. This study based on the FraudDiamond theory developed by Wolfe and Hermanson (2004). This study discussesmismanagement of fixed assets from the point of view of regional civil apparatus in theSemarang District Government. The population of this study is all regional civil apparatus inthe Semarang District Government by census method. This research was conducted usingprimary data. Primary data in this study used a questionnaire (questionnaire) to measure thevariables of financial pressure, habit pressure, work relationship pressure, pressure of otherfactors, perception of opportunity, general rationalization, authorization of functions,intelligence, ego and beliefs, coercion and fraud, ability to handle stress to fraud andmismanagement of fixed assets. The sample in this study amounted to 256 regional devices inthe Semarang District Government. The data obtained were analyzed by using multiple linierregression. Based on the results of the analysis carried out, it was concluded that 6variables: financial pressure, habit pressure, work relationship pressure, pressure of otherfactors, general rationalization, coercion and fraud to commit fraud had a positive effect tothe occurance possibility of mismanagement of fixed assets. Then, the ability to handle stresswhen committing fraud has a negative effect to the occurance possibility of mismanagementof fixed assets, while other variables namely perception of opportunity, position authorizationto commit fraud, intelligence to commit fraud and ego and confidence to commit fraud do nothave influence to the mismanagement of fixed assets by regional equipment.